2021
DOI: 10.2147/opth.s340041
|View full text |Cite
|
Sign up to set email alerts
|

Pentosan Polysulfate Sodium-Associated Pigmentary Retinopathy: Risk Factors and Fundus Findings

Abstract: Purpose To evaluate the risk factors and fundus findings of patients with potential PPS-associated retinopathy. Patients and Methods A retrospective chart review was performed of patients exposed to PPS who had a dilated fundus examination at a large retina-only practice from 2018–21. Multimodal images were evaluated by masked reviewers. Results A total of 148 patients were included, of whom 33 (22%) had PPS-associated retinopathy, and 115 (7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Common symptoms include blurred vision, difficulty reading, metamorphopsia, paracentral scotomas, and prolonged dark adaptation. Signs comprise parafoveal pigmented deposits at the level of the RPE, vitelliform deposits, and patchy paracentral RPE atrophy similar in appearance to pattern dystrophy [ 87 , 88 , 89 ]. Since PPS is an inhibitor of heparanase, used chronically, a study investigated the consequence of the absence of this enzyme in knockout mice (KO) [ 90 ].…”
Section: Drugs and Medicinementioning
confidence: 99%
“…Common symptoms include blurred vision, difficulty reading, metamorphopsia, paracentral scotomas, and prolonged dark adaptation. Signs comprise parafoveal pigmented deposits at the level of the RPE, vitelliform deposits, and patchy paracentral RPE atrophy similar in appearance to pattern dystrophy [ 87 , 88 , 89 ]. Since PPS is an inhibitor of heparanase, used chronically, a study investigated the consequence of the absence of this enzyme in knockout mice (KO) [ 90 ].…”
Section: Drugs and Medicinementioning
confidence: 99%
“…In an earlier interim evaluation of this study after the inclusion of 50 patients, Wang et al 9 reported a prevalence of pigmentary maculopathy associated with PPS of 20% (10 out of 50). According to the data provided, only two of these 10 (4%) patients had pigmentary maculopathy, according to the definition given by Pearce et al, 5 Hanif et al, 41 and Christiansen et al 42 A recent retrospective chart review performed by Leung et al 48 at a large retina-only practice showed that 33 (22%) of 148 patients with PPS exposure had signs of maculopathy. As none of these eyes fulfilled all the diagnostic criteria stipulated by Pearce et al, 5 Hanif et al, 41 and Christiansen et al, 42 no further conclusions can be drawn.…”
Section: Data On Prevalence Are Based On Several Prospective Cohort S...mentioning
confidence: 99%
“…To note, the maculopathy group had a higher mean cumulative dose of PPS and longer duration of PPS use (1,600±849 g versus 864±852 g; p<0.0001; and 13.6 years versus 7.48 years; p<0.0001, respectively). 48 Further indications on prevalence can be derived from the study by Ludwig et al, 11 as described above. The percentage of patients who received PPS and were later diagnosed with maculopathy is estimated to be 2.4%.…”
Section: Data On Prevalence Are Based On Several Prospective Cohort S...mentioning
confidence: 99%
“…7 Subsequent studies independently conducted at numerous centers have reported a significant dose-response relationship between PPS exposure and presence of maculopathy. [8][9][10][11][12][13] A study from 2020 demonstrated prevalence rates of 13%, 30%, and 42% among patients with 500-999 grams (g), 1000-1499 g, and >1500 g of cumulative PPS exposure, respectively. 8 In another study from earlier this year, researchers found prevalence rates of 46% and 83% among patients with cumulative PPS exposures of 1500-2000 g and ≥2000 g. 11 Studies of large administrative claims databases have yielded mixed findings.…”
Section: Strength Of Associationmentioning
confidence: 99%